Adherence to Guideline‐Recommended Therapy Is Associated With Decreased Major Adverse Cardiovascular Events and Major Adverse Limb Events Among Patients With Peripheral Arterial Disease - Armstrong, Ehrin J. (Blackwell Publishing Ltd, 2014)
BACKGROUND: Current guidelines recommend that patients with peripheral arterial disease (PAD) cease smoking and be treated with aspirin, statin medications, and angiotensin‐converting enzyme (ACE) inhibitors. The combined effects of multiple guideline‐recommended therapies in patients with symptomatic PAD have not been well characterized. METHODS AND RESULTS: We analyzed a comprehensive database of all patients with claudication or critical limb ischemia (CLI) who underwent diagnostic or interventional lower‐extremity angiography between June 1, 2006 and May 1, 2013 at a multidisciplinary vascular center. Baseline demographics, clinical data, and long‐term outcomes were obtained. Inverse probability of treatment propensity weighting was used to determine the 3‐year risk of major adverse cardiovascular or cerebrovascular events (MACE; myocardial infarction, stroke, or death) and major adverse limb events (MALE; major amputation, thrombolysis, or surgical bypass). Among 739 patients with PAD, 325 (44%) had claudication and 414 (56%) had CLI. Guideline‐recommended therapies at baseline included use of aspirin in 651 (88%), statin medications in 496 (67%), ACE inhibitors in 445 (60%), and smoking abstention in 528 (71%) patients. A total of 237 (32%) patients met all four guideline‐recommended therapies. After adjustment for baseline covariates, patients adhering to all four guideline‐recommended therapies had decreased MACE (hazard ratio [HR], 0.64; 95% CI, 0.45 to 0.89; P=0.009), MALE (HR, 0.55; 95% CI, 0.37 to 0.83; P=0.005), and mortality (HR, 0.56; 95% CI, 0.38 to 0.82; P=0.003), compared to patients receiving less than four of the recommended therapies. CONCLUSIONS: In patients with claudication or CLI, combination treatment with four guideline‐recommended therapies is associated with significant reductions in MACE, MALE, and mortality.